Meningkatkan Daya Saing UMKM melalui Penerapan Just-in-Time dan Teknologi Sederhana - Rusmina, Cut; Mawardi, Mawardi; M. Bakri; Susanti, Susanti; Radhiana, Radhiana; Aufal Surayya, Cut (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Small and medium-sized enterprises (SMEs) in the snack food sector face challenges such as limited capital, fluctuating raw material prices and intense market competition. This article aims to identify operational efficiencies and cost saving strategies to improve business competitiveness and sustainability. Using Just-In-Time (JIT) and Lean Production approaches, SMEs can reduce waste, cut costs and improve productivity without compromising quality. The analysis focuses on gaps in the adoption of modern technology, resource management and collaboration with suppliers and customers. The methodology includes the evaluation of production efficiency concepts and demand-driven supply chain optimisation. This article offers solutions such as the use of simple automation technologies, such as packaging machines, and a collaborative approach to strengthening supply chain relationships. The contribution of the article is to provide practical guidelines that integrate efficiency strategies, technological innovation and risk management. The expected outcomes are that SMEs will be able to improve productivity, reduce operating costs and create sustainable business models. This approach provides opportunities for SMEs to remain competitive in dynamic markets while supporting local economic growth.